Spice dehydration plant in Tarlac (a pre-feasibility study) - Tuazon, Raquel Porfiria Los Banos
A complete Technical Feasibility Study was done which covers the following: products and their characteristics: raw materials; manufacturing processes and schedules; rated capacity; equipment balance and specifications; plant location and layout; building facilities; utilities and waste; and personnel know-how. From the Financial Study the cost of the plant, the equipment and initial operating expenses total P 49,762,651.65 and an annual sales revenue of only P 16,263,100.00. The reason for this loss is the high cost of raw materials and the low selling price of the spices which cannot compete with the price of imported spices. From the Marketing Study the size of the market for spices which are the food processors, is favorable considering the growth in the food processing industry and the high volume of importation which can be replaced with locally produced spices. However the present production of the raw material is not enough to supply the dehydration plant which will greatly affect the supply to the market. Thus it will be feasible to establish the plant only if there is enough supply of raw material at a low cost and if the selling price of the product is just right to cover the costs and to compete with the imported spices. Contract and owned farming are suggested to cut the cost of the raw material and to enable a sufficient supply.